2020
DOI: 10.1097/hmr.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Advancing theory on the multilevel role of leadership in the implementation of evidence-based health care practices

Abstract: Our findings have implications for developing a multilevel leadership approach to implementation in health care. Leadership development should build on different competencies based on managers' level but align managers' priorities on the same implementation goals.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Leaders’ openness towards EBPs positively predicted implementation of medication-assisted treatment. * Guerrero et al 2020 [ 15 ] IL IC A Obs AH I IL was positively associated with provider's EBPA. IL did not mediate the relation among top leaders’ TfL and A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaders’ openness towards EBPs positively predicted implementation of medication-assisted treatment. * Guerrero et al 2020 [ 15 ] IL IC A Obs AH I IL was positively associated with provider's EBPA. IL did not mediate the relation among top leaders’ TfL and A.…”
Section: Resultsmentioning
confidence: 99%
“…Results from the qualitative synthesis are listed in Table 8 . Most studies (43%) examined the relationship between general leadership and an inner-context outcome [ 45 , 65 , 81 , 82 , 84 86 , 88 , 92 ], and fewer studies examined the relationship between strategic implementation leadership and an inner-context outcome (24%) [ 15 , 45 , 65 , 92 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation frameworks posit the importance of organizational leaders and their use of specific leadership behaviors as potential mechanisms to improve EBP implementation in healthcare settings [17][18][19][20]. These frameworks converge on the importance of leaders at multiple levels-from executives who make decisions about whether to implement an EBP to first-level leaders who directly supervise clinicians [21][22][23]-as well as on the importance of aligning leadership across levels [24][25][26]. Furthermore, many frameworks suggest the unique importance of first-level leaders, also known as middle managers, who directly supervise frontline clinicians [21,27].…”
Section: The Role Of First-level Leaders In Ebp Implementationmentioning
confidence: 99%
“…These implementation-focused leadership behaviors complement general transformational leadership; together, the two types of leadership contribute to a positive leader-follower relationship that is focused on the strategic imperative of effectively integrating EBP into care delivery [30]. Cross-sectional studies have shown that higher levels of implementation leadership among first-level leaders are linked to higher levels of EBP implementation climate [40,46,47] and superior clinician attitudes toward EBP [22]; however, we are unaware of any longitudinal studies that examine how implementation leadership changes over time or that link these changes to changes in EBP implementation climate.…”
Section: The Role Of First-level Leaders In Ebp Implementationmentioning
confidence: 99%